Problematic diagnosis of substance-induced disorders in ICD-11 - Bramness, Jorgen G.; Hjorthoj, Carsten; Niemelä, Solja; Taipale, Heidi; Rognli, Eline B. (CAMBRIDGE UNIV PRESS, 2025)
The ICD-11 was introduced in January 2022. In chapter 6, "Mental, behavioral and neurodevelopmental disorders" we find the section "Disorders due to substance use and addictive behaviors" (section 6C4). Changes from the ICD-10 in this section include broadening the categories of harmful use and dependence, including more types of substances, and the addition of more behavioral addictions (gaming disorder). These changes have been discussed and debated [1].